2020
DOI: 10.1101/2020.10.15.20122523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intravenous Mesenchymal Stem Cells in Extracorporeal Oxygenation Patients with Severe COVID-19 Acute Respiratory Distress Syndrome

Abstract: Background: There is an ongoing critical need to improve therapeutic strategies for COVID-19 pneumonia, particularly in the most severely affected patients. Adult mesenchymal stem cell (MSC) infusions have the potential to benefit critically ill patients with acute respiratory syndrome SARS-COV-2 infection, but clinical data supporting efficacy are lacking. Methods: We conducted a case-control study of critically ill patients with laboratory-confirmed COVID-19, severe acute respiratory distress syndrome (ARD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Finally, 13 studies reported in 14 articles were included for the study quality assessment and data analysis. 5 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 The study selection process and reasons for excluding studies are presented in Figure 1 .
Figure 1 PRISMA flow diagram for article selection.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, 13 studies reported in 14 articles were included for the study quality assessment and data analysis. 5 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 The study selection process and reasons for excluding studies are presented in Figure 1 .
Figure 1 PRISMA flow diagram for article selection.
…”
Section: Resultsmentioning
confidence: 99%
“… 37 For the dose, seven studies administered 1-3 × 10 6 cells per kg of body weight, 5 , 32 , 35 , 36 , 38 , 39 , 41 four studies administered 3-12 × 10 7 cells per infusion, 29 , 30 , 33 , 40 and two studies did not report the stem cell dose. 34 , 37 Among the 210 patients in the experimental group, 59 patients received a single dose, 5 , 32 , 36 , 39 , 41 35 patients received two doses, 35 , 37 , 40 and 116 patients received three doses of therapy. 29 , 30 , 33 , 34 , 35 , 38 All included studies applied intravenous (IV) as the route of delivery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With over 4,000,000 deaths worldwide and over 600,000 deaths in the USA out‐of‐box thinking is needed 4 . At our program in Miami COVID‐19 patients who have been on VV ECMO for more than 10 days or could not be weaned off VV ECMO after 4 weeks were offered work up for adult stem cell therapy and lung transplantation starting 2020 5 . Two COVID‐19 patients on VV ECMO were bridged to lung transplantation with a 50% 6 months survival including one case undergoing bilateral pneumonectomy on VV ECMO.…”
mentioning
confidence: 99%